Tracking behavioral persistence and innovations during the Middle Pleistocene in Western Europe. Shift in occupations between 700 and 450 ka at la Noira site (Centre, France). Issue 156 (July 2021) - Moncel, Marie-Hélène; García-Medrano, Paula; Despriée, Jackie; Arnaud, Julie; Voinchet, Pierre; Bahain, Jean-Jacques
Abstract: Some areas in Western Europe indicate hiatuses in human occupations, which cannot be systematically attributed to taphonomic factors and poor site preservation. The site of la Noira in the center of France records two occupation phases with a significant time gap. The older one is dated to around 700 ka (stratum a) with an Acheulean assemblage, among the earliest in Western Europe, and the upper phase of the sequence (stratum c) is dated to ca. 450 ka. Humans left the area at around 670 ka, at the beginning of the marine isotope stage (MIS) 16 glacial stage, when cold conditions became too severe. No sites between 650 and 450 ka have yet been discovered in the center region despite systematic surveys over the past three decades. The archaeological evidence indicates that populations returned to the area, at the end of MIS 12 or the beginning of the long interglacial MIS 11. Here, we use technological behaviors common to the two levels of la Noira—strata a and c to evaluate their differences. Compared to other key European sequences, this site can be used to address the evolution of the behavioral strategies in Europe between MIS 17 and 11. We formulate two hypotheses concerning the human settlement of this area: (1) local behavioral evolution over time of populations occasionally occupying the region when the climate was favorable or (2) dispersal and arrival of new populations from other areas. The results focus on (1) changes in land-use patterns with the extension of the territory used by hominins in the upper level, (2) the introduction of new core technologies, including some evidence of early Levallois debitage, and (3) more intensive shaping of bifaces and bifacial tools. Results attest that the la Noira archaeological assemblages record similar regional behavioral evolution as observed at a larger scale in Europe. Highlights: La Noira records two occupation phases with a time gap of 700–450 ka. Tracking common technological behaviors and innovations in Western Europe. Hypotheses on local filiation or arrival of new populations. Results focus on land use patterns, core technologies, and bifaces. Early evidence of Levallois.